Analysis of the Relationship between Stress and Dysmenorrhea in Female Students - Situmorang, Marlinawati; Anastasya, Margaretha (International Journal on ObGyn and Health Sciences, 2024)
This study investigates the relationship between stress and dysmenorrhea among female students, aiming to explore how perceived stress levels influence menstrual pain severity. A cross-sectional design was employed, involving 200 participants aged 18 to 25 years from a university setting. Participants completed validated surveys assessing perceived stress using the Perceived Stress Scale (PSS) and dysmenorrhea severity using the Visual Analog Scale (VAS). Results indicate a significant positive correlation between perceived stress levels and dysmenorrhea severity (r = 0.42, p < 0.001), highlighting that higher stress levels are associated with more intense menstrual pain. Subgroup analyses further reveal that academic pressures and poor sleep quality exacerbate this relationship. These findings underscore the importance of addressing stress management and promoting healthy lifestyle habits to improve menstrual health outcomes among female students. Future research should explore longitudinal designs to establish causal relationships and evaluate the effectiveness of stress reduction interventions in alleviating dysmenorrhea symptoms.